The Islamic Revolutionary Critique of Capitalism: A Study in the Context of Pakistan - Razzaq, Zain; Nawaz, Rab (International Journal of Islamic Economics and Governance, 2025)
In Pakistan, most Muslim thinkers view capitalism as just an economic system, overlooking its societal foundations. In contrast, the Islamic revolutionaries assert that capitalism is a totalizing, all-inclusive system and civilization, characterized by a specific conception of individual, society, and the authoritative structures (state), all of which are interconnected and mutually dependent. Islamic revolutionaries are thinkers and activists such as Mawdūdī and Ansari who consider Western ideologies and practices as conflicting with Islamic teachings and call for a complete societal transformation grounded in Islamic values. This study aims to explore the socio-political foundations of capitalism. This critique is crucial in Islamic political and economic thought, as it highlights the competitive relationship between Islam and capitalism by critically analyzing its socio-political foundation. The paper concludes that rather than attempting to Islamize capitalist economics, it is necessary to reject it. An analytical study method with a qualitative approach is employed in this paper. It prefers primary sources; however, secondary sources are also used when they are needed. © 2025 The Author(s). Licensed under CC BY-NC 4.0.